Dynamic elements of replication protein A at the crossroads of DNA replication, recombination, and repair. (2nd September 2020) - Caldwell, Colleen C.; Spies, Maria
Abstract: The heterotrimeric eukaryotic Replication protein A (RPA) is a master regulator of numerous DNA metabolic processes. For a long time, it has been viewed as an inert protector of ssDNA and a platform for assembly of various genome maintenance and signaling machines. Later, the modular organization of the RPA DNA binding domains suggested a possibility for dynamic interaction with ssDNA. This modular organization has inspired several models for the RPA-ssDNA interaction that aimed to explain how RPA, the high-affinity ssDNA binding protein, is replaced by the downstream players in DNA replication, recombination, and repair that bind ssDNA with much lower affinity. Recent studies, and in particular single-molecule observations of RPA-ssDNA interactions, led to the development of a new model for the ssDNA handoff from RPA to a specific downstream factor where not only stability and structural rearrangements but also RPA conformational dynamics guide the ssDNA handoff. Here we will review the current knowledge of the RPA structure, its dynamic interaction with ssDNA, and how RPA conformational dynamics may be influenced by posttranslational modification and proteins that interact with RPA, as well as how RPA dynamics may be harnessed in cellular decision making.